Effect of the Lights4Violence intervention on the sexism of adolescents in European countries - Belén Sanz-Barbero; Alba Ayala; Francesca Ieracitano; Carmen Rodríguez-Blázquez; Nicola Bowes; Karen De Claire; Veronica Mocanu; Dana-Teodora; Miriam Sánchez-SanSegundo; Natalia Albaladejo-Blázquez; Ana Sofia Antunes das Neves; Ana Sofia da Silva Queirós; et al. (BMC, 2022)
Abstract Background Sexism results in a number of attitudes and behaviors that contribute to gender inequalities in social structure and interpersonal relationships. The objective of this study was to evaluate the effectiveness of Lights4Violence, an intervention program based on promoting health assets to reduce sexist attitudes in young European people. Methods We carried out a quasi-experimental study in a non-probabilistic population of 1146 students, aged 12-17 years. The dependent variables were the difference in the wave 1 and wave 2 values in the subscales of the Ambivalent Sexism Inventory: benevolent sexism (BS) and hostile sexism (HS). The effect of the intervention was evaluated through linear regression analyses stratified by sex. The models were adjusted by baseline subscales scores, socio-demographic and psychological variables. Results In girls, we observed a decrease in BS in the intervention group compared to the control group (β = − 0.101; p = 0.006). In the wave2,, BS decreased more in the intervention group compared to the control group in girls with mothers with a low level of education (β = − 0.338; p = 0.001), with a high level of social support (β = − 0.251; p < 0.001), with greater capacity for conflict resolution (β = − 0.201; p < 0.001) and lower levels of aggressiveness (β = − 0.232, p < 0.001). In boys, the mean levels of HS and BH decreased in wave 2 in both the control and intervention groups. The changes observed after the wave 2 were the same in the control group and in the intervention group. No significant differences were identified between both groups. Conclusions The implementation of the Lights4Violence was associated with a significant reduction in BS in girls, which highlights the potential of interventions aimed at supporting the personal competencies and social support. It is necessary to reinforce the inclusion of educational contents that promote reflection among boys about the role of gender and the meaning of the attributes of masculinity. Trial registration Clinicaltrials.gov : NCT03411564 . Unique Protocol ID: 776905. Date registered: 26-01-2018.